Opportunities to Reduce Children's Excessive Consumption of Calories From Beverages. (October 2014) - Rader, Ryan K.; Mullen, Kathy B.; Sterkel, Randall; Strunk, Robert C.; Garbutt, Jane M.
Objective . To describe children's consumption of sugar-sweetened beverages (SSBs) and 100% fruit juice (FJ), and identify factors that may reduce excessive consumption. Design . A total of 830 parents of young children completed a 36-item questionnaire at the pediatricians' office. Results . Children consumed soda (62.2%), other SSBs (61.6%), and FJ (88.2%): 26.9% exceeded the American Academy of Pediatrics' recommended daily FJ intake. 157 (18.9%) children consumed excessive calories (>200 kcal/d) from beverages (median = 292.2 kcal/d, range 203.8-2177.0 kcal/d). Risk factors for excessive calorie consumption from beverages were exceeding recommendations for FJ (odds ratio [OR] = 119.7, 95% confidence interval [CI] = 52.2-274.7), being 7 to 12 years old (OR = 4.3, 95%CI = 1.9-9.9), and having Medicaid insurance (OR = 2.6, 95%CI = 1.1-6.0). Parents would likely reduce beverage consumption if recommended by the physician (65.6%). Conclusions . About 1 in 5 children consumes excessive calories from soda, other SSBs and FJ, with FJ the major contributor.